(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The current research paper deals with the evolution and geographical distribution and expansion of slums in the district of Faridabad. For this purpose, secondary sources of data have been used and presented using various methods and tools. Almost sixteen percent (fifty five percent males and forty five percent female) of the total population of Faridabad is residing in sixty-four slum clusters. Roughly twenty seven percent of the total population belongs to nscheduled caste category. A a severe disparity was also noticed regarding the literacy status and levels of the male and female populaton. Male population was more literate than their counterpart. To the great extent fast pace of industrialisation and urbanisation post-independence, is responsible for the evolution of the slums in this area. This area attracted migrants low-income groups from adjoining states.